Photocatalytic Activity and Wettability Properties of ZnO/Sawdust/Epoxy Composites - Safaa Ahmed Al-Lhaibi; Ban Mazin Al-Shabander (Iraqi Journal of Physics, 2022)
In this work, zinc oxide nanoparticles (ZnONPs) and sawdust/epoxy composite (20:80) were mixed using a simple molding method with different ZnONPs concentrations of (0.1, 0.3, 0.5, 0.7, and 1.0 %). The samples of the nanocomposites were characterized by the Scanning Electron Microscopy (SEM) technique to demonstrate the homogeneity of the prepared ZnONPs/nanocomposites. The photocatalytic activity of the samples was examined using the methylene blue (MB) dye as a pollutant solution, through evaluation of the efficiency of the prepared compound in the treatment of organic pollutants under illumination by sunlight. The photocatalytic results showed that after 240 minutes of exposure to sunlight, the sample prepared using (0.5 vol.% of ZnONPs) appeared to rapid degradation of MB dye, with photolysis efficiency of 89% and 71% for dye concentrations 5 and 10 ppm, respectively. Wettability results confirmed that the water contact angles of samples (WCAs) were affected by the concentration of ZnONPs.